The preliminary development and psychometric properties of the Psychotherapy Side Effects Scale - Fazhan, Chen; Liang, Liu; Xudong, Zhao; Qiang, Feng; Congcong, Ge; Yunhan, Zhao (Brain and behavior, 2023)
Background Side effects in psychotherapy are common and have a negative impact on patients or clients. However, effective evaluation tools are still lacking and have not been fully studied. The present study aims to develop a scale with good reliability and validity to measure the side effects of psychotherapy. Methods The 25 items in the Psychotherapy Side Effects Scale (PSES) were condensed and distributed to 420 subjects online to test its psychometric properties. Results The internal consistency of the PSES was satisfactory to excellent (Cronbach's ɑ coefficient was .95, and the Guttman split‐half coefficient was 0.88). A statistically significant negative correlation between the satisfaction score and the total score of the PSES was shown (r = −0.51, p < .001). The PSES could effectively discriminate between two groups with and without side effects (F = 250.95, p < .001) and was able to predict the occurrence of side effects in psychotherapy with an area under curve of 0.932 and a 95% confidence interval of 0.900–0.964 (p < .001). A cutoff was set at 36 points in total PSES score, from which the maximum Youden's index (= 0.72) could be obtained. The positive rate of the PSES was 24% (101/420). Conclusion The PSES showed good internal consistency, content validity, concurrent validity, discriminant validity and predictive validity in evaluating and identifying side effects in psychotherapy. More advanced reliability testing methods and structural validity testing for PESE need to be practiced in the future to better serve clinical practice.